Implementation of 5S Culture in Forming Students' Religious Character at SD Negeri 5, Banda Aceh City - Andika Mismal J; Siti Mayang Sari; Muhammad Iqbal (Journal of Education on Social Science (JESS), 2026)
This study aims to describe the implementation of the 5S culture (Smile, Greet, Greeting, Politeness, and Courtesy) in shaping the religious character of students at SD Negeri 5, Banda Aceh City. This research is based on the importance of instilling religious character in elementary school students as a foundation for spiritual, social, and moral attitudes in daily life. A qualitative descriptive approach was applied in this study. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the implementation of the 5S culture is carried out systematically and continuously through daily habituation activities in the school environment. The practice of smiling, greeting, and greeting is applied in interactions between teachers and students as well as between students. Meanwhile, politeness and courtesy are manifested in respectful behavior, the use of appropriate language, and compliance with school regulations. The implementation of the 5S culture has been proven to positively contribute to the formation of students' religious character, particularly in aspects of politeness, empathy, and respect for others. However, several challenges were identified, including inconsistent implementation and limited parental involvement at home. This study concludes that the 5S culture is effective in fostering religious character in students at SD Negeri 5, Banda Aceh City, through habituation and exemplary behavior demonstrated by the school community. The study recommends strengthening collaboration between schools and parents, as well as enhancing habituation programs to improve character building outcomes.